Giant axonal neuropathy: clinical and genetic study in six cases. Issue 6 (16th May 2005) - Demir, E; Bomont, P; Erdem, S; Cavalier, L; Demirci, M; Kose, G; Muftuoglu, S; Cakar, A N; Tan, E; Aysun, S; Topcu, M; Guicheney, P; et al.
Abstract : Background: Giant axonal neuropathy (GAN) is a severe recessive disorder characterised by variable combination of progressive sensory motor neuropathy, central nervous system (CNS) involvement, and "frizzly" hair. The disease is caused by GAN gene mutations on chromosome 16q24.1. Aims: To search for GAN gene mutations in Turkish patients with GAN and characterise the phenotype associated with them. Methods: Linkage and mutation analyses were performed in six affected patients from three consanguineous families. These patients were also investigated by cranial magnetic resonance imaging (MRI) and electroencephalography (EEG). Electromyography (EMG) was performed in heterozygous carriers from family 1 and family 3. Results: Linkage to 16q24.1 was confirmed by haplotype analysis. GAN mutations were identified in all families. Family 1 had the R293X mutation, previously reported in another Turkish family. Families 2 and 3, originating from close geographical areas, shared a novel mutation, 1502+1G>T, at the donor splice site of exon 9. All patients displayed a common phenotype, including peripheral neuropathy, cerebellar ataxia, and frizzly hair. Cranial MRI showed diffuse white matter abnormalities in two patients from family 1 and the patient from family 3, and minimal white matter involvement in the patient from family 2. EMG of a heterozygous R293X mutation carrier showed signs of mild axonal neuropathy, whereas a 1502+1G>T mutation carrier had normal EMG. EEG abnormalities were found in three patients. Conclusion: These findings highlight the association of CNS involvement, in particular white matter abnormalities, with peripheral neuropathy in GAN. The phenotypical consequences of both mutations (when homozygous) were similar.